2018
DOI: 10.1136/bmjopen-2017-019962
|View full text |Cite
|
Sign up to set email alerts
|

National mixed methods evaluation of the effects of removing legal barriers to full practice authority of Dutch nurse practitioners and physician assistants

Abstract: ObjectiveTo evaluate the effects of granting legal full practice authority (FPA) to nurse practitioners (NP) and physician assistants (PA) regarding the performance of specified reserved medical procedures and to support governmental decision-making.DesignNationwide mixed methods design with triangulation of quantitative (Pre-post test design) and qualitative data (expert interviews and focus groups).MethodsSurveys focused on the performance of the procedures (monthly number, authorisation mode, consultations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 59 publications
(33 reference statements)
3
22
0
1
Order By: Relevance
“…Based on experiences with the substitution in the field of nurse practitioners and physician assistants (who are performing medical procedures traditionally carried out by doctors), we expect that, due to the more effective and efficient use of everyone's competences, this overlap will decrease. 18 Another major change in the intended collaboration is that dental hygienist and dentist will work alongside each other, instead of the more hierarchical collaboration of the past. This requires new interprofessional collaboration skills.…”
Section: Introductionmentioning
confidence: 99%
“…Based on experiences with the substitution in the field of nurse practitioners and physician assistants (who are performing medical procedures traditionally carried out by doctors), we expect that, due to the more effective and efficient use of everyone's competences, this overlap will decrease. 18 Another major change in the intended collaboration is that dental hygienist and dentist will work alongside each other, instead of the more hierarchical collaboration of the past. This requires new interprofessional collaboration skills.…”
Section: Introductionmentioning
confidence: 99%
“…To enable effective task-shifting, it is important that any future PA regulation corresponds to the highest level of the PA's training. [34] The PA role is still emerging in Ireland and is being driven by similar factors as in other countries across the world: a shortage of physicians and workforce capacity [13,28,33] as well as a need for task shifting. [34] Thus, PAs are increasingly described as part of the solution to workforce shortages.…”
Section: Discussionmentioning
confidence: 99%
“…[34] The PA role is still emerging in Ireland and is being driven by similar factors as in other countries across the world: a shortage of physicians and workforce capacity [13,28,33] as well as a need for task shifting. [34] Thus, PAs are increasingly described as part of the solution to workforce shortages. The conversation on how to best improve healthcare delivery in Ireland continues, with one approach being restructuring surgical teams and exploring the expansion of roles such as the PA. [35,36] The Irish PA has the potential to expand to other settings and has been suggested for use in primary care, [37] which has been described in Ireland as under-sourced and as a crisis situation in the media.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that NPs do not have independent, full prescription rights in Switzerland yet, and educational programs still lack several hours on pharmacology compared to international standards, which could yield in hesitation of prescribing new drugs. De Bruijn-Geraets et al (39) found that prescription rates of Dutch NPs increased after obtaining full legal practice authority. However, during out-of-hours consultations, Van Der Biezen et al (30) found that NPs still prescribed less medications compared to GPs.…”
Section: Interpretation and Comparison To Existing Literaturementioning
confidence: 99%